KETERBATASAN ARGUMENTASI HAKIM DALAM SISTEM CIVIL LAW INDONESIA - Defika Yufiandra (CV Rewang Rencang, 2025)
In Indonesia's civil law system, judges are expected to apply legislation textually and mechanistically. However, this study shows judicial considerations are often influenced by non-juridical factors such as cognitive bias, psychological pressure, and structural limitations. The article analyzes three aspects: the influence of cognitive bias and judicial psychology, discretionary space between legality and justice based on Kelsen and Radbruch's thoughts, and structural pressures like caseload and judge shortage. Two case studies demonstrate how these factors limit legal reasoning quality. The conclusion emphasizes the need for structural reform, enhanced judicial capacity, and strengthened argumentative culture in the judicial environment.